SOFTWARE PROFICIENCY CRISIS IN HIGHER EDUCATION: A MULTI-PROGRAM ANALYSIS OF TECHNOMATHEMATICAL LITERACIES AND ITS PEDAGOGICAL IMPLICATIONS - Nailul Himmi; Zures Gustiabani; Sri Wahyuni; Nabilla Kurnia; Hasyara Nur’aini (Nurul Jadid University, 2026)
Engineering graduates increasingly need technomathematics literacy (TmL) and computational tools. However, empirical evidence on the multidimensional TmL profiles of students across engineering disciplines remains scarce. This study aims to assess the level of TmL of students in five engineering study programs and identify competency deficits as a basis for curriculum design improvements. The study used a quantitative, cross-sectional survey design with 135 first-semester students. Data were collected using a validated seven-dimensional TmL instrument. The results showed that the level of TmL was generally low (M = 2.32), with the Electrical Engineering study program achieving a moderate category (M = 2.64). The software capability dimension was the lowest (M = 1.91) across all programs. In contrast, analytical dimensions such as data literacy (M = 2.49) and error sensitivity (M = 2.46) were relatively higher. This confirms the gap between analytical and computational capabilities. These findings indicate that software competencies have not been optimally integrated into the curriculum, thus requiring the integration of computational-based problem-solving, strengthening lecturer capacity, and adjustments to accreditation standards to support the development of TmL as a graduate achievement.